Prevalence of overt myeloproliferative neoplasms and JAK2 V617F mutation in Korean patients with splanchnic vein thrombosis - YOO, E.-H.; JANG, J.-H.; PARK, K.-J.; GWAK, G.-Y.; KIM, H.-J.; KIM, S.-H.; KIM, D.-K. (International journal of laboratory hematology, 2011)
Summary Introduction:  Myeloproliferative neoplasm (MPN) is known to be a major risk factor of splanchnic vein thrombosis (SVT). Recent studies revealed that a significant proportion of patients with SVT harbor a gain‐of‐function mutation in the JAK2 gene (V617F) with or without MPN. In this study, the authors investigated the prevalence of MPN and JAK2 V617F mutation in Korean patients with SVT. Methods:  The study subjects were 26 patients diagnosed as having SVT based on Doppler ultrasound and/or computed tomography from January 2008 to January 2010 (16 men and 10 women; mean age 44 years, range 15–75 years). The clinical and laboratory data were reviewed. The JAK2 V617F mutation was detected by allele‐specific polymerase chain reaction and direct sequencing analyses using DNA from peripheral blood leukocytes. Results:  Among 26 study patients, 12 had portal vein thrombosis, five had hepatic vein thrombosis, three had mesenteric, and two had splenic vein thrombosis. Four patients had thrombosis involving more than one splanchnic vein. Two patients (7.7%; 2/26) had overt MPN (essential thrombocythemia). JAK2 V617F was detected in three patients (11.5%) including the two patients with overt MPN. Thus, the prevalence of the JAK2 V617F mutation in patients with SVT but without overt MPN was 4.2% (1/24). Conclusion:  The prevalence of overt MPN and that of JAK2 V617F were lower in Korean patients with SVT than in previous reports. Data from a larger number of patients with long‐term follow‐up are needed to reveal the clinical relevancy of JAK2 V617F in Korean patients with SVT.